Working together: making the case for integrated forensic services for people with intellectual disabilities. (14th December 2015) - MacMahon, Kenneth; McClements, Ricky
Abstract : Purpose: – There is a general consensus that healthcare for people with intellectual disabilities should be provided by multi-disciplinary teams. Within a forensic setting, recommendations are often made for separate or "parallel" forensic teams, operating independently of generic mental health or intellectual disability teams. An alternative to this model is an "integrated" service, where specialist forensic clinicians work within the general intellectual disability service, to provide support for clients with forensic needs. For clients with intellectual disabilities and forensic needs, there may be advantages to providing access to a wider multi-disciplinary team, through the application of an integrated model. The purpose of this paper is to illustrate the working of an integrated forensic service within a learning disability team, to identify positive aspects of this model, and how potential shortcomings may be overcome. Design/methodology/approach: – Literature review, description of service outline with case example. Findings: – Although some studies have compared parallel and integrated forensic models within mental health services, there are no evaluations that compare models of forensic services for individuals with intellectual disabilities. However, specific advantages of an integrated model may include availability of multi-disciplinary clinicians, development of forensic skills across wider groups of clinicians, reduction in stigma and avoidance of delay in transfer of care between services. In addition, in areas with smaller populations, parallel services may not be feasible due to low case numbers. Originality/value: – There has been no formal evaluation of parallel vs integrated forensic services within an intellectual disability setting. However, the authors describe a fully integrated service and suggest means by which the potential shortcomings of an integrated model may be overcome.